(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotatsiya:Islom moliyasining O’zbekistondagi ahamiyati qanday? Foiz bo’lmasa, foyda qayerdan keladi? Undan kimlar foydalana oladi? Islom iqtisodiyoti vositalaridan faqat musulmon bo’lganlar foydalanishi mumkinmi? Annotation: what is the importance of Islamic finance in Uzbekistan? Where does the profit come from if there is no interest? Who can use it? Can the tools of Islamic Economics be used only by those who are Muslims?